Seasonality and intensity of airborne Boletus-type spores in relation to land use and weather pattern - Magdalena Wójcik; Idalia Kasprzyk (IMA Fungus)
Abstract Forests are a natural source of airborne bolete spores. The timing of sporulation and its intensity as well as the dispersal of airborne spores and in consequence their concentrations depend in particular on the type of land use determining the availability of matter on which they develop and on meteorological factors. The aim of this study was to perform a spatial and temporal analysis of the occurrence of Boletus-type spores in the warm temperate climate of the Northern Hemisphere. An assumption was made that the spore concentrations depend on the type of land cover and weather conditions. The volumetric method was applied to investigate differences in spore concentrations and using spore traps installed at different heights and at locations with different land cover types. Boletus-type spores occurred in the air at high concentrations in late summer and in the autumn. The season start dates and maximum concentrations did not differ significantly between sites and seasons, but the season intensity varied. Higher spore concentrations were usually found in the region with a larger proportion of green areas, including forests. An analysis of the diurnal cycles showed that within 24 h spore concentration reached high levels twice, which was especially noticeable in ground level monitoring. Air temperature and air humidity were the main weather factors affecting the occurrence of airborne spores. This research indicates that when studying the effects of different factors on the concentration of airborne basidiospores, many environmental elements should be analyzed, including the characteristics of habitats in which basidiomycetes grow. Climate, weather, geobotany, and land use type should be taken into account in analysis and interpretation of aeromycological phenomena.